La notion de bourgeoisie dans l’historiographie de la Turquie contemporaine - David Behar (Revue des Mondes Musulmans et de la Méditerranée)
This article presents a case for historiographic discontinuity between the Ottoman and Turkish Republican eras as the principal cause for the failure to develop a sociology of the Turkish bourgeoisie. Indeed, understanding the mechanisms governing the reconversion of resources and the distribution of privileges requires a distinction between the old and the new, because there is a legitimate time for wealth. Such a sociology is essential to understanding the major social, economic and political changes which have occurred in Turkey over the past thirty years. The analysis of the uses, even if sometimes contradictory, of the concept of bourgeoisie in contemporary Turkish historiography opens new prospects. This paper shows that a complete renewal of Turkish elites has not occurred, since a segment of this group is described by historians as possessing the attributes of a “bourgeoisie”. Studies of the Turkish bourgeoisie for both the final years of the Ottoman Empire and the Republican period indicate a number of points of continuity. In the present context, it is thus possible to isolate a group of families who display the characteristics of a “upper bourgeoisie”, which is to say capital accumulations in all possible economic, cultural, social and symbolic forms.